Catch per unit effort of estuarine push net with emphasis on occurrence and abundance of acetes shrimps in the coastal waters of Malacca, Peninsular Malaysia - Sarker, Mohammad Nurul Amin; Arshad, Aziz; Shamsudin, Sarikha; Bujang, Japar Sidik; Siraj, Siti Shapor (Universiti Putra Malaysia Press, 2008)
Catch per unit effort (CPUE) of estuarine push net (EPN) and abundance of Acetes shrimps in the coastal waters of Klebang Besar, Malacca were investigated based on thecatch data from April 2006 to March 2007. The average monthly CPUE of the EPNobserved was 3.53 (±3.99) kg/fisherman/hour. The total catch comprised of three majorcategories namely: Acetes shrimps (90%), fish juveniles (9%) and other shrimps (1%). Amongst the Acetes shrimps, three species (A. indicus, 87%, A. japonicus, 12% and A.intermedius, 1%) were recorded from the investigated area. The peak catches wereobserved during the months of September, November and December. There was nosignificant correlation (p > 0.05) between monthly catches and environmental parameters (temperature, dissolved oxygen, salinity and pH).